(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2026)
United Nations (UN) documents represent one of the most influential forms of institutional communication in contemporary international relations. While previous studies have primarily focused on lexical, syntactic, and pragmatic characteristics of diplomatic discourse, comparatively little attention has been paid to paralinguistic features embedded within official documents. This article examines the role of paralinguistic and graphological elements in the construction of meaning within United Nations documentation. Drawing upon theories of discourse analysis, institutional communication, and paralinguistics, the study argues that visual and textual features—including typography, formatting conventions, punctuation patterns, capitalization, numbering systems, document structure, and multimodal components— contribute significantly to the interpretation of diplomatic texts.